Dielectric and electrical response of hydroxyapatite – Na0.5K0.5NbO3 bioceramic composite - Verma A.S.; Kumar D.; Dubey A.K. (My University, 2025)
In recent years, the development of electrically active materials for orthopedic implant applications attracted attention owing to the fact that inherent electricity of bone mediates it's various metabolic processes. In this perspective, the present work investigates the effect of incorporation of varying amounts of piezoelectric biocompatible Na0.5K0.5NbO3 (NKN) on dielectric and electrical properties of hydroxyapatite (HA) over a wide range of temperature (30–500 °C) and frequency (1 Hz – 1 MHz). The composites HA-x NKN (x = 10–30 wt%) were synthesized by solid state ceramic method and optimally sintered at 1075 °C for 2 h. X-Ray Diffraction (XRD) and Fourier Transform Infrared (FTIR) patterns confirmed the formation of phase pure HA and NKN in the composite system. The dielectric response of the samples has been compared with that of the existing theoretical models. The dielectric measurement suggests that the space charge as well as dipolar polarization is the dominant polarization mechanisms. The complex plane impedance and modulus spectroscopic analyses were performed to reveal the conduction mechanism. The activation energies for grain and grain boundary resistance for HA- (10–30 wt%) NKN were 1.03, 1.464, 1.28 and 1.34, 1.56, 1.30 eV, respectively. These results suggest that ionic conduction is the dominant conduction mechanism. Hydroxyl ions and oxygen vacancies are observed to be responsible for the conduction in HA-xNKN composite system. Overall, HA- x NKN composite system can be suggested as a potential material for electro-active orthopedic implant application. © 2018 Elsevier Ltd and Techna Group S.r.l.